Factors influencing adoption of new wheat techniques in Wolmera and Addis Alem areas of Ethiopia - Yirga, C.; Shapiro, Barry I.; Demeke, M. (1996)
A study was conducted in two woredas, Addis Alem and Wolmera, to investigate (1) the level of farmers' awareness and adoption of recommended and demonstrated technologies; (2) the extent and intensity to which farmers have adopted these technologies; and (3) the objective and subjective factors affecting adoption. A total of 156 farmers were randomly selected and interviewed using a pre-tested questionnaire. The study showed that the vast majority of the surveyed farmers had reached the state of continuous adoption: about 89 percent for fertilizer, 79 percent for herbicide and 49 percent for new improved varieties of wheat. Although fertilizer and herbicide (2,4-D) are widely used in the study areas, average fertilizer and herbicide application were well below the recommended rate for all the crops. The Probit and Tobit regression models were used for this study and the results indicated that the perceived profitability of the new wheat technologies and the timely availability of fertilizer and herbicide had the most significant effect on farmers' decisions to adopt. Distance of respondents' homes from extension centers also influenced the probability of adopting improved wheat variety, as well as the intensity of fertilizer and herbicide use. Characteristics of the household and household heads had little influence on the adoption decisions of these farmers. This suggests that improved production packages have been extensively diffused so that the knowledge of the benefits of using the new technologies is widespread. Moreover, extension efforts and input availability are most crucial in influencing adoption.